Identification of mouse and human embryonic pancreatic cells with adult Procr+ progenitor transcriptomic and epigenomic characteristics - Heidenreich, Ana C.; Bacigalupo, Lucas; Rossotti, Martina; Rodríguez-Seguí, Santiago A. (Frontiers in Endocrinology, 2025)
BackgroundThe quest to find a progenitor cell in the adult pancreas has driven research in the field for decades. Many potential progenitor cell sources have been reported, but so far this is a matter of debate mainly due to reproducibility issues. The existence of adult Procr+ progenitor cells in mice islets has been recently reported. These were shown to comprise ~1% of islet cells, lack expression of Neurog3 and endocrine hormones, and to be capable of differentiating into all endocrine cell types. However, these findings had limited impact, as further evidence supporting the existence and function of Procr+ progenitors has not emerged.Methods and findingsWe report here an unbiased comparison across mouse and human pancreatic samples, including adult islets and embryonic tissue, to track the existence of Procr+ progenitors originally described based on their global gene expression signature. We could not find Procr+ progenitors on other mouse or human adult pancreatic islet samples. Unexpectedly, our results revealed a transcriptionally close mesothelial cell population in the mouse and human embryonic pancreas. These Procr-like mesothelial cells of the embryonic pancreas share the salient transcriptional and epigenomic features of previously reported Procr+ progenitors found in adult pancreatic islets. Notably, we report here that Procr-like transcriptional signature is gradually established in mesothelial cells during mouse pancreas development from E12.5 to E17.5, which has its largest amount. Further supporting a developmentally relevant role in the human pancreas, we additionally report that a transcriptionally similar population is spontaneously differentiated from human pluripotent stem cells cultured in vitro along the pancreatic lineage.ConclusionsOur results show that, although the previously reported Procr+ progenitor cell population could not be found in other adult pancreatic islet samples, a mesothelial cell population with a closely related transcriptional signature is present in both the mouse and human embryonic pancreas. Several lines of evidence presented in this work support a developmentally relevant function for these Procr-like mesothelial cells.